Forty Years After the Islamic Revolution of Iran: An Indonesian Perspective - Dicky Sofjan (Religió: Jurnal Studi Agama-agama, 2019)
Following 40 years of Khomeini’s Islamic Revolution in Iran, how does Indonesia view Iran then and now? Is the exportation of the Revolution now relevant amid the contemporary political constellation in the Middle East and the world? Does Shia Islam remain to pose a sociopolitical problem today in the largest Muslim nation? In view of the current political standoff with the United States of America, will the system, based on Velayat-e Fagheh (Guardianship of the Jurist), remain strong against all odds? This article explores these questions based on personal reflections, experiential learning and continuous engagement in and with Iran.